Cardiorespiratory fitness, screen time, and parents’ educational level as predictors of academic performance among adolescents in Majorca - Bennàsser Torrandell, Martí Xavier; Vidal-Conti, Josep (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Knowing which variables can predict the Academic Performance (AP) is of great interest to improve learning outcomes. The aim of the study was to determine whether parents’ academic education, as well as weekly hours of Physical Activity (PA), Maximum Volume of Oxygen (VO2max), and Screen Time (ST), can predict the AP of adolescents. The study included 2399 young people aged 10 to 16 years from Mallorca (1224 girls, 51%, and 1175 boys, 49%). In coordination with various schools, a questionnaire on sports habits was administered to the participants. The Course Navette test was administered to estimate the VO2 max., besides the students’ AP was provided by the school. The results showed that being younger (β = - 0.170; p = 0.001), being a girl (β = -0.354; p = 0.001), having better Cardiorespiratory Fitness (CF) (β = 0.046; p < 0.001), having parents with a higher academic education (β = 0.673; p < 0.001), and spending less ST on weekdays (β = - 0.039; p = 0.001), predict a better AP in adolescents. Future studies investigating a predictive link between different healthy lifestyle behaviors, various socio-personal variables, and their relationship with AP, are important for strengthening the findings of this and similar studies.